Meneruskan Tradisi: Upaya Pelestarian Kearifan Lokal Tape di Kalangan Generasi Muda - Siti Nihar Salsabilah; Khoirun Nisak; Ahmad Khiori (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
This article discusses the local wisdom of tape as one of Indonesia's rich and unique cultural heritages. Tape, made from fermented base ingredients such as cassava, serves not only as food but also holds deep social and cultural values. In this context, the article explores the process of making tape, the traditions surrounding it, and its role in strengthening the identity of local communities. Furthermore, the article highlights the importance of preserving the local wisdom of tape amid the currents of modernization and globalization that threaten the existence of traditional cultures. The research method employs a qualitative approach with interview and observation techniques. This study aims to raise awareness of the importance of appreciating and preserving cultural heritage, as well as encouraging the younger generation to engage in these valuable traditional practices.